Platinum(ii) alkyl complexes of chelating dibridgehead diphosphines P((CH2)n)3P (n = 14, 18, 22); facile cis/trans isomerizations interconverting gyroscope and parachute like adducts. Issue 36 (1st September 2021) - Zhu, Yun; Ehnbom, Andreas; Fiedler, Tobias; Shu, Yi; Bhuvanesh, Nattamai; Hall, Michael B.; Gladysz, John A.
Abstract : The dibridgehead diphosphines P((CH2 ) n )3 P can serve either as cis or trans spanning chelate ligands. Reactions of trans PtCl 2 adducts and RLi (2 equiv.) give only cis PtR2 adducts, which upon reaction with HCl (1 equiv.) revert to trans PtRCl adducts. Abstract : The gyroscope like dichloride complexes trans -Pt(Cl)2 (P((CH2 ) n )3 P) ( trans -2 ; n = c, 14; e, 18; g, 22) and MeLi (2 equiv.) react to yield the parachute like dimethyl complexes cis -Pt(Me)2 (P((CH2 ) n )3 P) ( cis -4c, e, g, 70–91%). HCl (1 equiv.) and cis -4c react to give cis -Pt(Cl)(Me)(P((CH2 )14 )3 P) ( cis -5c, 83%), which upon stirring with silica gel or crystallization affords trans -5c (89%). Similar reactions of HCl and cis -4e, g give cis / trans -5e, g mixtures that upon stirring with silica gel yield trans -5e, g . A parallel sequence with trans -2c /EtLi gives cis -Pt(Et)2 (P((CH2 )14 )3 P) ( cis -6c, 85%) but subsequent reaction with HCl affords trans -Pt(Cl)(Et)(P((CH2 )14 )3 P) ( trans -7c, 45%) directly. When previously reported cis -Pt(Ph)2 (P((CH2 )14 )3 P) is treated with HCl (1 equiv.), cis - and trans -Pt(Cl)(Ph)(P((CH2 )14 )3 P) are isolated (44%, 29%), with the former converting to the latter at 100 °C. Reactions of trans -5c and LiBr or NaI afford the halide complexes trans -Pt(X)(Me)(P((CH2 )14 )3 P) ( trans -9c, 88%; trans -10c, 87%). Thermolyses and DFT calculations that include acyclic model compounds establish trans > cis stabilities for all except the dialkyl complexes, for which energies can be closely spaced. The σ donor strengths of the non-phosphine ligands are assigned key roles in the trends. The crystal structures of cis -4c, trans -5c, trans -7c, and trans -10c are determined and analyzed together with the computed structures.